Biomimetic reconstruction of butterfly wing scale nanostructures for radiative cooling and structural coloration. Issue 9 (1st July 2022) - Lee, Jinwoo; Jung, Yeongju; Lee, MinJae; Hwang, June Sik; Guo, Jiang; Shin, Wooseop; Min, JinKi; Pyun, Kyung Rok; Lee, Huseung; Lee, Yaerim; Shiomi, Junichiro; Kim, Young-Jin; et al.
Abstract : The butterfly wing scales of several species exhibit dual functionalities of radiative cooling and structural coloring. Here, we artificially reconstruct a butterfly wing scale of periodically grating nanostructures with extremely high porosity. Abstract : A great number of butterfly species in the warmer climate have evolved to exhibit fascinating optical properties on their wing scales which can both regulate the wing temperature and exhibit structural coloring in order to increase their chances of survival. In particular, the Archaeoprepona demophon dorsal wing demonstrates notable radiative cooling performance and iridescent colors based on the nanostructure of the wing scale that can be characterized by the nanoporous matrix with the periodic nanograting structure on the top matrix surface. Inspired by the natural species, we demonstrate a multifunctional biomimetic film that reconstructs the nanostructure of the Archaeoprepona demophon wing scales to replicate the radiative cooling and structural coloring functionalities. We resorted to the SiO2 sacrificial template-based solution process to mimic the random porous structure and laser-interference lithography to reproduce the nanograting architecture of the butterfly wing scale. As a result, the biomimetic structure of the nanograted surface on top of the porous film demonstrated desirable heat transfer and optical properties for outstanding radiative cooling performance and iridescent structural coloring. In this regard, the film is capable of inducing the maximum temperature drop of 8.45 °C, and the color gamut of the biomimetic film can cover 91.8% of the standardized color profile (sRGB).